2021
DOI: 10.3390/antibiotics10081006
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomics-Based Analysis of the Age-Related Cumulative Effect of Antibiotic Resistance Genes in Gut Microbiota

Abstract: Antibiotic resistance in bacteria has become a major global health problem. One of the main reservoirs of antibiotic resistance genes is the human gut microbiota. To characterise these genes, a metagenomic approach was used. In this study, a comprehensive antibiotic resistome catalog was established using fecal samples from 246 healthy individuals from world’s longevity township in Jiaoling, China. In total, 606 antibiotic resistance genes were detected. Our results indicated that antibiotic resistance genes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 88 publications
0
21
0
Order By: Relevance
“…This is the first large-scale retrospective trial of abnormal blood glucose metabolism in China, including high blood glucose group and normal blood glucose group. The clinical evidence of the effect of WMT on blood glucose metabolism has been established, which lays the foundation for subsequent studies on the effects of gut microbiota (53), metabolic markers (54), and diet (55) regulation on abnormal blood glucose metabolism. Taken together, these results suggest that restoring gut microbiota may serve as a promising treatment for abnormal blood glucose metabolism; however, the mechanism of action requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first large-scale retrospective trial of abnormal blood glucose metabolism in China, including high blood glucose group and normal blood glucose group. The clinical evidence of the effect of WMT on blood glucose metabolism has been established, which lays the foundation for subsequent studies on the effects of gut microbiota (53), metabolic markers (54), and diet (55) regulation on abnormal blood glucose metabolism. Taken together, these results suggest that restoring gut microbiota may serve as a promising treatment for abnormal blood glucose metabolism; however, the mechanism of action requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This is a large-scale retrospective trial of MS in southern China, including a MS group and a non-MS group. The clinical evidence of the effect of WMT on MS has been established, laying a foundation for the follow-up study of the effects of gut microbiota ( Wu et al., 2021b ) and metabolic markers ( Wu et al., 2022b ) on metabolic abnormalities. Taken together, these results suggest that restoring gut microbiota may serve as a promising treatment for MS; however, the mechanism of action requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This was A. indonesiensis as well, but showed in vitro activity against aminoglycosides, tetracyclines, imipenem, and ceftriaxone [ 10 ]. Recently, Wu et al [ 11 ] identified, in a metagenomic approach, a genus Acetobacter in human fecal samples as one of the main genera carrying the top 20 antibiotic resistance gene types. So far, there are no data on the AMR of Komagataeibacter species.…”
Section: Introductionmentioning
confidence: 99%